ELEKTRİK YANIKLARINDA TERMAL ETKİ VE ADALE PERFÜZYONU - DEMİR, Mustafa; KALKAN, M. Tunaya; ŞENER, Osman; AHMED, Sabbir; SAYMAN, Haluk; ÇETİNKALE, Oğuz; USLU, İlhami (Cerrahpaşa Medical Journal, 2014)
Background and Design.- In this study, the pattern of thermal change in animal.s bone and tissue after exposed to an electric shock have been studied. Wistar Albino male rats with body weight in range 300-350 gr were used in the experiment. To apply electric shock to the body of the rat, positive electrode was attached to the front left leg, and negative electrode to the back right leg. At first, the left front and right back legs of 10 rats injecting 74 MBq Tc-99m MIBI were examined, and then scintillation images were performed under normal condition of tissue. In the normal phase, scintillation images of the same organs were taken injecting same amount of radiopharmaceutical after applying an electric shock with 220 volt AC supply, for a duration of 10 seconds with an amount of 100 mA current. Post-shock stages at 1 hr, 24 hr, 48 hr and 72 hours were monitored. 10 rats were studied for each above stage. To measure the thermal change in bones, fluoroptic thermometer was used. The total counts from the burning region (ROI) were measured by gamma camera and the thermal changes of the extremities were obtained from the thermometers attached to the front left leg and to the back right leg both in soft tissue and on the surface of bone. Results.- It was found that the thermal increases were 3.1±0.8°C in the front thermometer and 6.2 ±1.2°C in the back thermometer. The shock effects exhibited maximum change in the soft tissue within 1 hr. but these effect disappeared rapidly there after. The ratio of counts between front and back leg at different time interval were calculated and was compared to that of normal stage. ie. before giving electric shock. It was found that the prolonged damage of tissue showed significant changes with the probability p<0.001 and p<0.0001 after 48 and 72 hours by using Students t-test. Conclusion.- In conclusion, it.s precise to mention that electrical shock effect exhibits minimum change in tissue within 24 hr. when the medical treatment may affect within this period. The cells tend to exhibit some permanent changes gradually.